Exploring the Toxicity of Lateral Violence and Microaggressions Poison in the Water Cooler (Springer International Publishing, 2018)
Examining the subtle forms of aggression, violence, and harassment that occur in our society and manifest in institutions and places of work, the expert contributors collected here describe the experience of social marginalization and expose how vulnerable individuals work to navigate exclusionary climates. This volume explores how bodies disrupt the status quo in multiple contexts and locations; provides insights into how institutions are structured and how practices that may cause harm are maintained; and, finally, considers progressive and proactive alternatives. This book will be a key resource for academics and professionals in education, sociology, nursing, law, business and political science, as well as organizations and policymakers grappling with aggression in the workplace.